Islamic law review on use of Go-Pay in payment of Zakat - Laila Afni Rambe (Sultang Agung Islamic University, 2020)
Technological developments turned out to have a major influence on changes in community economic transactions. The system that was once used by the community is a manual system but technological developments bring it to change into an online system that all transactions can be done without having to face to face, without being influenced by time and place. So, that the community is spoiled by the system. Not only in the scope of economic transactions around trade, but this online system has also been used in zakat payment transactions that use electronic money. The purpose of this research is to see how the legal use of electronic money when used to pay zakat. To achieve the objectives of this study the authors use the method of library research, namely by examining documents both published officially or contained in all printed materials, or in electronic form relating to the topics discussed. From the results of the analysis conducted by the author on these data it can be concluded that electronic money Go-Pay may not be used because it is not in accordance with the provisions of DSN-MUI. When electronic money or Go-Pay should not be used, Go-Pay also should not be used to pay zakat.